Modeling of 185W of mono-crystalline solar panel using MATLAB/Simulink - Jumaat, Siti Amely; Liang, Ong Wei; Abdullah, Mohd Noor; Radzi, Nur Hanis; Hamdan, Rohaiza; Salimin, Suriana (Institute of Advanced Engineering and Science, 2019)
This paper presents a modeling of 185W Mono-crystalline Solar Panel Using Matlab/Simulink approach. The objective of this project to carried out the efficiency and performance of Solar Panel. The type of solar panel in this project is a mono-crystalline by the SC Origin Company. A temperature and irradiance are the input parameters of the system. The outputs of the system are voltage, current and power. In addition, the data of temperature and irradiance from August to December 2017 by RETScreen Website. This data are used as an inout for PV System and the curve of I-V and P-V as the output. The data are collected at location 1.86° N, 103.09° E which is in Bandar Penggaram, Johor. The output result of I-V and P-V will be used to compare with the reference.